2022
DOI: 10.25267/hachetetepe.2022.i24.1101
|View full text |Cite
|
Sign up to set email alerts
|

Formación del profesorado universitario en Competencia Digital: análisis con métodos de investigación correlacionales y comparativos

Abstract: The global crisis caused by the current COVID19 pandemic has placed the distance teaching-learning process at the centre of educational practices at all educational stages, making clear the importance of training university teaching staff in digital competences. Given this approach, the purpose of this study is to analyse the use of ICT resources focused on teaching, learning and research tasks by Spanish Higher Education teaching staff according to gender, as well as the influence of certain academic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
1
0
3
Order By: Relevance
“…Lockdown has revealed that the digital competence of both teachers and students is, in many cases, still far from reaching the necessary levels, at least for didactic purposes (Prendes, Gutiérrez Porlán & Martínez Sánchez, 2018;Guillén, Ruiz Palmero, Palacios Rodríguez & Martín Párraga, 2021;Viñoles-Cosentino, Sánchez-Caballé & Esteve-Mon, 2022). The development of all the knowledge that is necessary in an environment of uncertainty would allow teachers to be more critical of their activity, and to grow professionally (Cabero-Almenara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Lockdown has revealed that the digital competence of both teachers and students is, in many cases, still far from reaching the necessary levels, at least for didactic purposes (Prendes, Gutiérrez Porlán & Martínez Sánchez, 2018;Guillén, Ruiz Palmero, Palacios Rodríguez & Martín Párraga, 2021;Viñoles-Cosentino, Sánchez-Caballé & Esteve-Mon, 2022). The development of all the knowledge that is necessary in an environment of uncertainty would allow teachers to be more critical of their activity, and to grow professionally (Cabero-Almenara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…En resumen, en este trabajo se evidencia la necesaria formación del profesorado en cuestiones técnicas, pero sobre todo pedagógicas, tal y como también sucede en profesorado de Educación Superior (Guillén-Gámez et al, 2022). Una de las limitaciones de este trabajo es el uso de una base de datos, y la otra es la falta de uso de altimétricas, que pueden ayudar a conocer la repercusión social de trabajos e investigadores (Sixto-Costoya et al, 2019).…”
Section: Conclusionesunclassified
“…En el caso que nos ocupa, la Competencia Digital puede entenderse como una forma de usar las tecnologías, así como comprender el impacto de ellas en el mundo digital, promoviendo su integración óptima (S.A. NMC, 2017). Según Guillén-Gámez et al (2022), la Competencia Digital Docente, hace referencia a las diferentes destrezas relacionadas con el uso de las herramientas y tecnologías en el contexto de aula. Está relacionada con todas aquellas habilidades, actitudes y conocimientos requeridos por los docentes en un mundo digitalizado.…”
Section: Innoeduca International Journal Of Technology and Educationa...unclassified